A Sustainable Indoor Air Quality Monitoring Approach through Potable Living Wall for Closed Confined Spaces: A Way Forward to Fight Covid19 - Tabbasum, Faiza; Shah, Syed Muzzamil Hussain; Teo, Fang Yenn; Mustaffa, Zahiraniza; Aleem, Muhammad Faique; Khan, Hammad Ahmed; Tariq, Shehroz; Haseeb, Abdul; Hamza, Syed Mohammad; Alam, Noman (Universitas Diponegoro, 2023)
The COVID-19 pandemic has greatly influenced various aspects of life, part of which has consequently paved the way toward improvements in building design criteria, especially for closed confined spaces. The closed confined spaces are directly proportional to the quantity and quality of the volatile organic compounds (VOCs) present in the atmosphere, from which human beings breathe. In managing the impact produced by VOCs, a practical, sustainable, economical and environmentally friendly concept of indoor living walls has become a prominent feature for improving the indoor air quality (IAQ) of closed confined spaces to efficiently reduce sick building syndrome (SBS) factors. In modification of common practice of ventilation systems, living wall technology leverages the natural ability of plants to purify indoor air quality by reducing air pollutants and allows the recycling of indoor air and the creation of a productive and inspiring environment. In this paper, the concept of a portable living wall through the use of a native plant species locally available in Sindh, Pakistan is introduced. Herein, the portable living concept was assessed by means of the design, construction, and data collection (testing and monitoring) of various environmental parameters carried out before and after the installation of the living wall. The study was monitored for 90 days, and analyses for various types of air pollutants were carried out in the environmental laboratory. During the monitoring period, the parameters humidity, VOCs, hazardous chemicals of concern (HCOC), CO2 and CO showed reductions in their values, with changes observed ranging from 61.5 to 58%, 0.66 to 0.01 ppm, 0.2 to 0.01 ppm, 1070 to 528 ppm and 0.2 to 0.01 ppm, respectively. The outcomes showed noticeable changes in air pollutants coupled with reductions in heating, ventilation and air conditioning (HVAC) energy consumption by up to 25%, mainly due to limited air requirements for ventilation.